2019
DOI: 10.3390/ijerph16081335
|View full text |Cite
|
Sign up to set email alerts
|

Construction Worker Risk-Taking Behavior Model with Individual and Organizational Factors

Abstract: Behavioral-based safety is an important application of behavioral science that can be used to address safety problems in the construction sector. An understanding of construction worker risk-taking behavior is deemed to be a crucial basis on which concerned authorities and construction companies can develop effective safety interventions to reduce construction accidents. However, no studies have been conducted to examine the effects of safety climate, work condition, attitude toward risk, cognitive bias, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…Secondly, future studies should also explore how UWB-based RTLS could be used along with other safety prevention methods to make construction sites even safer. For instance, risk-taking behavior of construction is common and is a cause of construction accidents [45,46]. Studies may explore how UWB-based RTLS could be used to compliment behavior-based safety to reduce such risk-taking tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, future studies should also explore how UWB-based RTLS could be used along with other safety prevention methods to make construction sites even safer. For instance, risk-taking behavior of construction is common and is a cause of construction accidents [45,46]. Studies may explore how UWB-based RTLS could be used to compliment behavior-based safety to reduce such risk-taking tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…The previous related studies generally concluded that fall from heights on construction sites is one of the most important reasons [ 11 ]. Scholars also conducted explorations about reasons of resulting in construction hazards from different perspectives such as ergonomic evaluations of suspension brackets [ 12 , 13 ], electrical applications [ 14 ], steel structures [ 15 ] and risk-taking behavior [ 16 ]. Recently, safety climate significantly influences safety performance, making research in the field of safety climate a vital step toward raising safety levels at construction sites [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, social groups often influence workers' unsafe behaviors through social organizational factors, such as safety training, behavior feedback, and so on. Most previous literature has directly studied the impact of social organizational factors on workers' unsafe behaviors based on macro-level correlation, statistical analysis, and empirical interpretation [26,29]. When social organizational factors change, it is difficult to predict how safety behavior will change.…”
Section: Introductionmentioning
confidence: 99%